2020
DOI: 10.1093/pubmed/fdaa170
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 antibodies in residents of Karachi—challenges in acquiring herd immunity for COVID 19

Abstract: Background The recent pandemic by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global emergency. There is large number of asymptomatic cases of SARS-CoV-2 that are not reported. Hence, serological evidence of SARS-CoV2 antibodies is warranted for a better estimation of the actual number of infected patients to limit the disease spread and to get an idea of herd immunity. Methods This is a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Our results are consistent with an assessment of flu-like symptoms amongst healthcare workers in India during the same period ( Jha et al, 2020 ), but contrast with the findings of serology studies in Delhi and other urban South Asian settings, which indicate a high proportion of the populations tested may have been infected with COVID-19 during the lockdown ( ero-prevalence st, 2020 ; (2020). TheR, 2020 ; Zaidi et al, 2020 ). These observations suggest that a high proportion of people in South Asia may be infected asymptomatically, in keeping with the younger age distribution of South Asian populations, compared to European or North American countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with an assessment of flu-like symptoms amongst healthcare workers in India during the same period ( Jha et al, 2020 ), but contrast with the findings of serology studies in Delhi and other urban South Asian settings, which indicate a high proportion of the populations tested may have been infected with COVID-19 during the lockdown ( ero-prevalence st, 2020 ; (2020). TheR, 2020 ; Zaidi et al, 2020 ). These observations suggest that a high proportion of people in South Asia may be infected asymptomatically, in keeping with the younger age distribution of South Asian populations, compared to European or North American countries.…”
Section: Discussionmentioning
confidence: 99%
“…7 The age structure of the population and under-reporting of deaths are both proposed as possible reasons for the lower value, but other data from Asia also indicate high rates of asymptomatic infections. 8 Within the wider context of the pandemic are several local epidemics at different stages of progression. The higher seroprevalence in urban areas and areas with an influx of migrants indicate that high contact rates probably fuelled the rapid spread of the virus.…”
Section: Tracking Sars-cov-2 Infection In India With Serologymentioning
confidence: 99%
“…Several research studies have suggested that some L&MICs might have moderate to high levels of infection. Seroprevalence studies in Qatar [3] , Manaus (Brazil) [4] , Pakistan [5] , South Africa [6] and Nairobi (Kenya) [7] reported finding antibodies for SARS-CoV-2 in large percentages of the studied populations. Estimates of actual deaths due to COVID-19, combined with estimates of expected mortality rates, similarly suggest that SARS-CoV-2 has infected large shares of the populations in several L&MICs [8] , including Bolivia, Ecuador, Peru, Mexico and South Africa [9] , Sudan [10] , Syria [11] , Yemen [12] and Zambia [13] .…”
Section: Introductionmentioning
confidence: 99%